Limitation of therapeutic effort experienced by intensive care nurses - Velarde-García, Juan Francisco (Nursing ethics, 2018)
Background:Nurses who practice limitation of therapeutic effort become fully involved in emotionally charged situations, which can affect them significantly on an emotional and professional level.Objectives:To describe the experience of intensive care nurses practicing limitation of therapeutic effort.Method:A qualitative, phenomenological study was performed within the intensive care units of the Madrid Hospitals Health Service. Purposeful and snowball sampling methods were used, and data collection methods included semi-structured and unstructured interviews, researcher field notes, and participants’ personal letters. The Giorgi proposal for data analysis was used on the data.Ethical considerations:This study was approved by the Ethical Research Committee of the relevant hospital and by the Ethics Committee of the Rey Juan Carlos University and was guided by the ethical principles of voluntary enrollment, anonymity, privacy, and confidentiality.Results:In total, 22 nurses participated and 3 themes were identified regarding the nurses’ experiences when faced with limitation of therapeutic effort: (a) experiencing relief, (b) accepting the medical decision, and (c) implementing limitation of therapeutic effort.Conclusion:Nurses felt that, although they were burdened with the responsibility of implementing limitation of therapeutic effort, they were being left out of the final decision-making process regarding the same.